Patients with Asthma May Develop Cardiovascular Diseases during Covid-19 Lockdown Due to Physical Inactivity - Abubakar, Ibrahim Ahmad; Muhammad, Daha Garba (Journal of Pharmacy Practice and Community Medicine)
To abate the spread of coronavirus, decisions were made one of which is restrictions of movement and public gatherings. This has led to drastic increase in poor lifestyle behaviours that are detrimental to health such as physical inactivity, these behaviours augment the risk of cardiovascular diseases (CVDs) in individuals including patients with asthma. Asthma is well established as a risk factor for developing CVDs. Patients with asthma were physically inactive, limiting outdoor activities and regular physical activities during COVID-19 lockdown makes them more inactive. Therefore, these pandemic exposed individuals who are asthmatic to high risk of developing CVDs.
Keywords: Asthma; CVDs; Covid-19; Poor lifestyle; Physical inactivity